Valley-Hall slow-light waveguide states with dual-band in all-dielectric valley photonic crystals - Liu He; Jianquan Yao (Results in Physics)
The slow-light waveguide states protected by topology could be used in strengthening interaction between light and matter, so they can be used for realizing a lot of unique physical optics phenomena and interesting applications. In this work, we consider a kind of all-dielectric valley photonic crystals (VPCs) with honeycomb lattice, realize dual-band photonic valley-Hall kink states at the stacking interface composed of two VPCs with mirror symmetry through breaking the parity-reversal symmetry of photonic system, such as low-frequency and high-frequency valley-Hall kink states. The valley-Hall kink states can be classified two categories: guided states and slow-light states, which depends on the magnitude of group index ng. By full-wave simulations, we directly observe that the dual-band valley-Hall slow-light states are in a way of standing-wave-liked modes to transport along the interface, and the more group index ng is, the half-wavelength λL/2 of standing-wave-liked is longer. Based on numerical calculation, the largest group indexes of low-frequency and high-frequency valley-Hall slow-light waveguide states are 1000, 1378, respectively. Hence in theory we can use half-wavelength λL/2 of standing-wave-liked modes to characterize slow-light states instead of judging respond time or fitting dispersion curve, which provides an alternative method or road to directly observe and demonstrate slow-light waveguide states in experiment.